IMPLEMENTATION CHARACTER AND MORAL EDUCATION ON ONLINE LEARNING PROCESS IN DARUL ULUM PRIMARY SCHOOL BABADAN, PONOROGO - Neri Wijayanti; Rindang Diannita (International Conference on Social and Islamic Studies, 2021)
Moral and character education is a process of applying moral values ​​and character to students through science. These values ​​are applied to oneself, family, fellow friends to educators and the surrounding environment as well as to God Almighty. Elementary school age children have increased social development, which initially only socializes with family at home, then becomes acquainted with the people around them.  Because of this, elementary school-age children already need to inculcate moral and character education in their learning. But in this pandemic period, because learning is done online, educators find it difficult to implement moral and character education in their learning. This happens not only in state elementary schools but also in Islamic elementary schools in Indonesia such as MI and SDIT. The purpose of this study is to describe moral and character education in online or online learning and to find out the supporting and inhibiting factors in learning at MI Darul Ulum, Babadan District, Ponorogo Regency, East Java. This research method uses a qualitative approach with a single case study. Collecting data using in-depth interviews, observation, documentation and qualitative descriptive data analysis. This research was conducted during the COVID-19 pandemic and is expected to be a new reference for learning in Elementary Schools during the pandemic which is carried out online so that even though learning is done online, the moral and character education in it will remain and will not be lost during this pandemic.